The Enhancing Maternal Confidence Through Controlled Childbirth: A Holistic Community-Based Approach in Beru-Beru Village: Enhancing Maternal Confidence Through Controlled Childbirth - Aya, Nurhidaya; Dwi Ghita; Susi Rabuana (Journal Kiara : Nursing and Midwifery, 2025)
Physical and psychological readiness of pregnant women plays a crucial role in ensuring a smooth delivery process and a positive childbirth experience. However, in Beru-Beru Village, Kalukku District, low levels of readiness are still observed, influenced by limited knowledge, socio-cultural factors, and traditional beliefs. This activity aimed to improve maternal knowledge and physical as well as psychological readiness through health education using leaflet-based media. The implementation method included a pre-test, delivery of educational material, discussion, post-test, and subsequent monitoring and evaluation. The program involved 32 participants, including expectant mothers, pregnant women, community health volunteers, and family members. The results showed a significant increase in knowledge, from 40.6% of participants with good knowledge in the pre-test to 93.8% in the post-test, representing a 53.2% improvement. Leaflet-based education proved effective in enhancing understanding and readiness for childbirth. This program is expected to serve as a sustainable intervention model to reduce delivery complications, increase maternal confidence, and promote a positive childbirth experience.